Strategi Marketing Pada Pemasaran Penjualan Handphone di Store Samsung Surabaya - Saremben, Anjela Rini Wanti; Fadhillah, Is (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the marketing strategy in selling cellphones at Samsung Surabaya Store. This research uses a qualitative approach, with research subjects consisting of employees of the marketing and sales marketing staff at the Samsung Surabaya Store. Data were obtained through interviews, observations, and documentation, which were then analyzed descriptively qualitatively. The results of this study indicate that the marketing strategy for selling cellphones at the Samsung Surabaya Store uses four marketing mix strategies, namely: product, price, promotion, and place. In addition, this study also identified factors that support and hinder sales marketing. Supporting factors include good management, good service, and support from the community. Meanwhile, the inhibiting factors consist of internal and external factors.